Ultrasound-based assessment of spinal muscle thickness and elasticity in patients with idiopathic scoliosis - Lei, Huangwei; Meng, Lin; Sun, Yifan; Gou, Yanyun (The Ultrasound Journal, 2025)
Purpose: Utilizing ultrasonic imaging technology, this study assessed and compared the thickness and elasticity features of the abdominal and spinal back muscles in patients with idiopathic scoliosis to those of healthy individuals. The objective was to elucidate the mechanical adaptations in spinal muscles among IS patients. Methods: This cross-sectional study included 38 patients diagnosed with idiopathic scoliosis and 33 healthy controls. Outcome measures comprised the Cobb angle, spinal curvature, muscle thickness, and muscle elasticity. Ultrasound elastography imaging was employed to assess the thickness and elasticity of the erector spinae, rectus abdominis, external oblique, and transverse abdominis muscles bilaterally at corresponding spinal levels. The objective was to document and compare the ultrasonic imaging characteristics of these muscles in individuals with idiopathic scoliosis and in the normal population. Results: The study findings indicated that idiopathic scoliosis patients had significantly lower body weight than the control group, with C7-CSVL notably greater in the idiopathic scoliosis group than in healthy individuals. Muscle thickness was substantially reduced on both the concave and convex sides at T6, T10, and L3 levels of the erector spinae, as well as in the rectus abdominis (RA) and transverse abdominis (TrA) muscles, relative to the normal cohort. Additionally, idiopathic scoliosis patients exhibited increased elasticity in the erector spinae muscle on the convex side at T6, while the elasticity of the erector spinae muscle on the concave side at L3 was significantly lower compared to healthy individuals. Conclusions: This study, utilizing ultrasound elastography imaging technology, unveiled distinct features in individuals with mild idiopathic scoliosis, including decreased muscle thickness in the erector spinae at T6, T10, and L3 levels, as well as heightened elasticity in the thoracic region and reduced elasticity in the lumbar region. The findings presented in this study provide insights for diagnostic strategies in individuals with early-stage scoliosis.